Axiology and phraseology of policy for small farms in Poland and the European Union - Wilkin, Jerzy (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2013)
There is a mass phenomenon of small, semi-subsistence farms in the European Union. Most of these farms are located in the new member states joining the EU in 2004 and in 2007 (notably in Romania and Poland), additionally there are also many such farms in Italy, Greece and Portugal. Solving the problem of small farms is a difficult task without an evident solution in many states, including Poland. Current EU intervention supports small farms using the instruments of the Common Agricultural Policy (CAP), and also addresses a group of households, but the efficiency and effectiveness of these activities is low. This article analyses both axiological premises policy of small farms, as well as practical solutions for this problem. It concludes that there is a need for a comprehensive and innovative policy for small farmers on a national scale, this, to a large extent independent of the CAP.
Keywords: small farms; Common Agricultural Policy; the Polish agriculture; agricultural policy axiology; phraseology policy